Cardiac arrest associated with non-toxigenic corynebacterium diphtheria strain: A case report - George V. Alvarez; Deborah D. Rupert; Samantha Sinclair; Santiago J. Miyara; Santiago J. Miyara; Sara Guevara; Peter Shih; Cynthia Hoey (Frontiers in Medicine, 2023)
Here we document a rare, acute, infection caused by non-toxigenic Corynebacterium diphtheriae and the resulting unique and severe clinical sequelae. Our patient was a young man with no known pre-existing conditions that presented in cardiopulmonary arrest. We contrast this case with prior instances of non-toxigenic C. diphtheriae strain infection in the United States and summarize the literature that suggests systemic infection can result in cardiogenic toxicity. We speculate on a possible missed, pre-existing condition that could have increased this patient’s susceptibility to poor clinical outcome.